Proficiency Enhancement of KVK-Scientists: Illustrating the Capacity Development Needs in Andhra Pradesh and Tamil Nadu - Geetha M; Ananthan P.S.; Bhaskaran A; Shivaji D Argade; Naila M Bhat (Journal of Indian Fisheries Association, 2024)
Krishi Vigyan Kendras (KVK) provide a basket of extension and advisory services and act as bridge between research and extension systems at the district level. The present study assessed the information and training needs of 62 SMSs of the KVKs in Andhra Pradesh and Tamil Nadu through an online survey. Training needs were collected on a three-point continuum scale and ranked using the Weighted Sum Method (WSM). The majority of the respondents were men and belonged to the age group of <35 years and possessed a PhD (58%), of which 19% had specialisation in fisheries. About three-fifth of SMS spent significant and adequate time on extension work (61%), perceived the available budget to be adequate (58%), and infrastructure to be inadequate (76%). Reportedly, interaction with colleagues (53%) and digital media (51%) are the primary sources of technical information, and 71% expressed the need for the development of user-friendly technical material to aid in extension work. Recent Technologies in Aquaculture (14.67) and Success story documentation (9.33) were the most preferred topics of training by the SMS of Tamil Nadu and Andhra Pradesh, respectively. Spearman’s correlation showed no significant association between the training needs of the SMS and their profile variables as well as the perceived organisational climate. Most SMS preferred offline trainings (60%) with a preferred duration of 5-7 days (45%) and a fee structure of Rs. 2500 (52%). Attention of the KVK administrators (ICAR ATARI and SAUs) and KVK coordinators is drawn to the findings of the study to design tailored competency enhancement programs for SMS to make them deliver extension services, especially in the field of fisheries and aquaculture, more effectively.